Factors Behind the Unrelenting Perseverance of the Minorities at the Marginal Status at Wolaitta Zone, Southern Ethiopia - Mengesha, Akalework (European Scientific Journal, ESJ, 2017)
This article has managed to critically assess factors behind the unrelenting perseverance of the minorities at the margin of marginal status at Wolaitta zone, Southern Ethiopia. The study identifies basically the validation behind the persisted disadvantaged position of the occupational minorities that is embedded within the socio-cultural scenery of Woliatta. It has attempted to explain the marginal status of the occupational minorities in the face of altering socio-economic and political state of contemporary society. A cross sectional qualitative method was used (in-depth interviews and focus group discussions) involving a total of 42 in-depth interview informants, 5 focus group discussions constituting 7 individuals in each group carried out in purposively selected sites. It has been discovered that there are certain sections of society that are considered to be of lower status and thus, marginalized and excluded from the host community. The minority groups that occupy the subordinate stratum include Hilancha-craft workers and ‘Ayille’social groups. These sections of the society have made to occupy the perimeter in essential societal activities and institutions. In other words, it’s been branded that occupational groups are at the verge of social, economic and political spheres of the mainstream society. They are detested and relegated in all aspects of their life.